Antropologiczno-kulturowy wymiar sportu w nauczaniu Jana Pawła II = Anthropological and cultural aspect of sport in teaching of John Paul II - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article titled ?Antropological and cultural aspect of sport in teaching of John Paul II? begins with reflection upon personalistic concept of human being by Karol Wojtyla ? John Paul II, as well as with his own sport activities. Human being, according to the pope, is above all a person. Thus, as the respective author reasons, sport that helps to improve oneself is important part of human life.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; sport